Dynamic Regulation of Synaptic Transmission onto Serotonin Neurons by Antidepressants - Geddes, Sean D (Université d'Ottawa / University of Ottawa, 2012)
Antidepressants are generally believed to exert their clinical efficacy by enhancing 5-HT transmission. Interestingly, sustained administration of selective serotonin (5-HT) reuptake inhibitors (SSRIs) strongly suppresses in the first few days the firing activity of 5-HT neurons in the dorsal raphe nucleus (DRN), thereby severely hampering the increase of 5-HT in target regions. Remarkably, the firing activity of 5-HT neurons gradually recovers over the time course of treatment and this recovery is believed to be accounted for by the desensitization of 5-HT1A somatodendritic autoreceptors. Here, we sought to investigate whether additional mechanisms might contribute to the dynamic regulation of excitability of 5-HT neurons during the course of SSRI treatments. Borrowing from the well-described homeostatic strengthening of glutamatergic synapses onto cortical pyramidal neurons following prolonged periods of inactivity, we hypothesized that a similar homeostatic-like regulation of synaptic strength might be operant on 5-HT cells during an SSRI treatment. To test this possibility, we used whole-cell electrophysiological recordings on acute midbrain slices to monitor glutamatergic synapses onto 5-HT neurons. We found that a two-day treatment with the SSRI citalopram induced a robust reduction in both the amplitude and frequency of AMPAR-mediated mEPSCs. We also show that this depression in synaptic strength, induced by an SSRI, is transient since excitatory drive onto 5-HT neurons was enhanced by 7 days of treatments. Altogether, these results document a dynamic regulation of glutamatergic synaptic transmission during the time course of a prolonged treatment with an SSRI. Further elucidation of the cellular and molecular mechanisms driving this synaptic plasticity might identify novel pharmacological target to shorten the delay of antidepressant action.
Keywords: Electrophysiology; Glutamate; NMDAR; AMPAR; Serotonin; SSRI; Whole-Cell Recording